2012
DOI: 10.1111/j.1365-313x.2012.05088.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar membrane transporters OsVIT1 and OsVIT2 modulate iron translocation between flag leaves and seeds in rice

Abstract: SUMMARYThe plant vacuole is an important organelle for storing excess iron (Fe), though its contribution to increasing the Fe content in staple foods remains largely unexplored. In this study we report the isolation and functional characterization of two rice genes OsVIT1 and OsVIT2, orthologs of the Arabidopsis VIT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
301
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(326 citation statements)
references
References 46 publications
13
301
0
1
Order By: Relevance
“…In fact, Leitenmaier and Kupper (2011) show that metal storage in leaf epidermis cells is a rate-limiting step in metal hyperaccumulation, but it is not the only process that governs metal accumulation despite its role as an important driving force behind the complex phenomenon of metal hyperaccumulation. Several membrane transporters (e.g., HMA and VIT) have been proposed to play an important role in vacuolar sequestration (Morel et al, 2009;Zhang et al, 2012b).…”
Section: E Chelation and Compartmentation In Leavesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Leitenmaier and Kupper (2011) show that metal storage in leaf epidermis cells is a rate-limiting step in metal hyperaccumulation, but it is not the only process that governs metal accumulation despite its role as an important driving force behind the complex phenomenon of metal hyperaccumulation. Several membrane transporters (e.g., HMA and VIT) have been proposed to play an important role in vacuolar sequestration (Morel et al, 2009;Zhang et al, 2012b).…”
Section: E Chelation and Compartmentation In Leavesmentioning
confidence: 99%
“…Other MTPs also contribute to Mn transport (Gustin et al, 2011). Furthermore, it seems that the tonoplast-localized transporters OsVIT1 and OsVIT2 participate in Mn influx to the vacuole (Zhang et al, 2012b). Regarding vacuolar export, AtNRAMP3 and AtNRAMP4 are expressed in the tonoplast and can transport Mn and other metals (Lanquar et al, 2010).…”
Section: Manganese Uptake By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that disruption of OsVIT1 or OsVIT2 enhanced iron translocation between the source and sink organs, and proposed this as a novel strategy for producing iron-biofortified rice. Zhang et al (2012) and Bashir et al (2013) reported that the cadmium concentration was also increased following VIT knockdown in rice. Therefore, this approach should be avoided in cadmium-contaminated soils.…”
Section: Iron Biofortification In Plantsmentioning
confidence: 99%
“…Kim et al (2006) reported that the Arabidopsis vacuolar iron transporter, VIT1, is highly expressed in developing seeds, and it transports Fe and Mn into the vacuole. Zhang et al (2012) reported that disruption of the rice VIT orthologs (OsVIT1 and OsVIT2) increased the iron concentrations by 1.4-fold in brown seeds, and it decreased the iron concentrations by 0.8-fold in the source organ flag leaves because VIT genes are highly expressed in rice flag leaves. Bashir et al (2013) reported that an OsVIT2-knockdown mutant showed 1.3-fold and 1.8-fold increases in iron concentrations in the brown and polished rice seeds, respectively.…”
Section: Iron Biofortification In Plantsmentioning
confidence: 99%